The Water Monitoring System in Flood Alert Level Design Based on Internet of Things (IoT) - Ally Akbar Salim; Emilia Hesti; Lindawati (Politeknik Piksi Ganesha Indonesia, 2022)
This study aimed to produce a flood alert system that can monitor water-levels in watersheds based on the Internet-of-Things (IoT), using the NodeMCU ESP8266 as a microcontroller and connecting internet connections. The main hardware used was a probe sensor as a water-level detector, an LED as a water level indicator, an LCD displaying the water level status, and a nodeMCU ESP8266 as a processor for the probe sensor detection results and sending information on the water-level status to the Telegram on Android. The status consisted of a safe level when the water level was at 1.5 m, an alert status was at 2 m, and a hazard status was at 3 m. When the water surface touched the probe sensor, nodeMCU ESP8266 read and processed the detection results. Then the status information was sent to Telegram and displayed on the LCD.